The Impact of Gender Stereotypes and Self-Efficacy on the Glass Ceiling Phenomenon in the Religious Affairs Office of Purwakarta Regency - Nia Kurniasih; Neuneung Ratna Hayati (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
This study aimed at gender stereotypes and self-efficacy as determinants of the glass ceiling effect. Data was collected through questionnaires distributed to employees in the office. The linear regression analysis method is used to analyze the data. Office of the Ministry of Religious Affairs of Purwakarta District. The results showed that Gender Streotypes partially had a significant influence on Glass Ceiling, Self-Efficacy had a significant influence on Glass Ceiling. The implications of these findings are discussed in the context of the Importance of addressing Gender Stereotypes in the workplace: Organizations need to be aware of the impact of Gender Stereotypes on the Glass Ceiling and take steps to reduce or eliminate those stereotypes